The Development of Web-Based Interactive Learning Media on Static Electricity Materials With Tutorial Model - Mahardika, Andi Ichsan; Purba, Harja Santana; Permana, Arief (Kasuari: Physics Education Journal (KPEJ), 2022)
In the learning process, the learning media acts as a tool. Along with the development of technology, various learning media in the learning process can be used. This study aims to develop web-based interactive learning media on static electricity class IX with a tutorial model and analyze the feasibility of the media in terms of validity, practicality, and effectiveness. The development of learning media uses research and development methods with ADDIE development procedures. Data collection techniques using validity assessment, questionnaires, and tests. The results showed that: (1) this learning media was built using HTML, CSS, Javascript, JSON, and Firebase technologies. (2) the learning media is declared valid in terms of the assessment of the validity of the material and media, practicality in terms of student and teacher response questionnaires is declared practical, effectiveness in terms of student learning outcomes tests with a classical completeness percentage of 80%. Based on the results of the study, it can be concluded that web-based interactive learning media on static electricity class IX with a tutorial model is appropriate to be used as a learning tool.